1985
DOI: 10.1007/bf00397387
|View full text |Cite
|
Sign up to set email alerts
|

Waxmonoester fermentation in Euglena gracilis T. Factors favouring the synthesis of odd-numbered fatty acids and alcohols

Abstract: Waxmonoester fermentation at the expense of endogenous paramylon was followed in the dark in autotrophically grown Euglena gracilis. With reduced oxygen tension and decreasing O2-consumption rates the proportion of odd-numbered fatty acids and alcohols increased up to a molar ratio of nearly 1:1 under strictly anaerobic conditions. Labelled (14)CO2, succinate and propionate were incorporated into odd-numbered fatty acids and alcohols 11 to 33 times faster than in even-numbered chains. The electron-flow inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…Wax ester fermentation by Euglena is similar in general principle to the synthesis of branched shortchain fatty acids in Ascaris or butyrate in Dasytricha: fatty acids are synthesized from acetyl-CoA condensation with an acyl-CoA (starting with acetyl-CoA or propionyl-CoA), a reduction of the resulting 3-oxoacid to 3-hydroxy acid, dehydration thereof, and a reduction of the resulting trans-enoyl-CoA to the elongated acylCoA. In contrast to malonyl-CoA-dependent fatty acid synthesis, the acetyl-CoA-dependent Euglena route allows net fermentative ATP synthesis from glucose, because acetyl-CoA is condensed without prior ATP-dependent carboxylation to malonyl-CoA (213,215,443). The step catalyzed by trans-2-enoyl-CoA reductase (NADPH dependent) circumvents the reversal of an O 2 -dependent step in ␤-oxidation (197).…”
Section: Fig 13mentioning
confidence: 99%
“…Wax ester fermentation by Euglena is similar in general principle to the synthesis of branched shortchain fatty acids in Ascaris or butyrate in Dasytricha: fatty acids are synthesized from acetyl-CoA condensation with an acyl-CoA (starting with acetyl-CoA or propionyl-CoA), a reduction of the resulting 3-oxoacid to 3-hydroxy acid, dehydration thereof, and a reduction of the resulting trans-enoyl-CoA to the elongated acylCoA. In contrast to malonyl-CoA-dependent fatty acid synthesis, the acetyl-CoA-dependent Euglena route allows net fermentative ATP synthesis from glucose, because acetyl-CoA is condensed without prior ATP-dependent carboxylation to malonyl-CoA (213,215,443). The step catalyzed by trans-2-enoyl-CoA reductase (NADPH dependent) circumvents the reversal of an O 2 -dependent step in ␤-oxidation (197).…”
Section: Fig 13mentioning
confidence: 99%
“…Rhodoquinone Levels in Euglena Change with Oxygen Availability-In wax ester fermentation in Euglena mitochondria, the synthesis of even-numbered fatty acids starts from acetylCoA, whereas odd-numbered fatty acid synthesis starts from propionyl-CoA, which is generated via succinate, propionate, and methylmalonyl-CoA (21,56,57). The formation of propionyl-CoA involves fumarate reductase, which catalyzes the reverse reaction of that in succinate dehydrogenase (complex II) but requires the lower midpoint potential of rhodoquinone versus ubiquinone to function efficiently in the succinate-synthesizing direction (2,13,58,59).…”
Section: Proteomic Studies Reveal An Anaerobic Response In Euglenamentioning
confidence: 99%
“…Although we have provided evidence of a reductive pathway from OAA to succinate in this alga during anaerobiosis, we do not know the relative flux of carbon between the oxidative and reductive paths of the TCAC. We therefore do not know the significance of the reductive pathway in the maintenance of oxidative TCAC carbon flow relative to other potential processes such as H2 evolution (9,10 (16) and in Euglena (27). It has been shown that fumarate reduction may be linked to NADH oxidation and ATP synthesis (7 and references therein) thereby providing an excellent strategy for anaerobic fermentation.…”
Section: Reductive Tcac Carbon Metabolism During Anaerobiosismentioning
confidence: 99%